Study on the Perception and the Role Performance of the Convenors of Group Farming Committees of Rice Cultivation - Jayasree Menon (Department of Agricultural Extension, College of Horticulture, 1993)
The study on role perception and role performance of the convenors of Group Farming Committee was carried out using 150 respondents selected from Trichur and Palghat districts. The opinions of respondents towards the programme were collected by personally interviewing them Analysis of the data thus collected indicated that cosmopoliteness and training need were the most important independent variables positively influencing role perception. Training revceived by the convenors exerted a negative effect on the perception of their roles as convenors. Communication behaviour came first followed by knowledge and training need among the independent variables influencing role performance. In the case of role perception as well as role performance, constraints in implementing the programme exerted maximum indirect effect on other independent variables. It was also found that role perception was strongly correlated with role performance.